FNG PANEL Confort térmico por medio de micelio - Patiño Soto, José Manuel (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Biomaterials and biofabrication are two recently developed concepts. Mycelium is part of this growing family of emerging materials that aims to reduce ecosystem degradation, extend the lifecycle of certain natural materials such as plant biomass, and, above all, reintegrate them into ecosystems without the pollution associated with hydrocarbon derivatives. It is important to note that these materials have a manufacturing cycle where the carbon footprint is minimal; many of them are crafted manually in laboratories, and those produced industrially generate low CO2 emissions. This work focuses on studying the qualities and possibilities of living organisms from the Fungi kingdom for creating biofabricated pieces that demonstrate mechanical, thermal, and aesthetic properties. The options offered by this world in its various species and their interaction with the plant biomass they feed on for the creation of new materials are explored. A material option is provided, applicable to architecture with a sustainable approach, aimed at reusing abundant waste materials that can fit into a circular economy and the concept of territory.

Los Biomateriales y la Biofabricación son dos conceptos de reciente creación. El micelio forma parte de esta creciente familia de materiales emergentes que busca reducir el deterioro de los ecosistemas, aumentar el ciclo de vida de algunos materiales naturales como las biomasas vegetales y, sobre todo, reintegrarlos a los ecosistemas sin la contaminación que ocurre con los derivados de hidrocarburos. Es importante tener en cuenta que estos materiales tienen un ciclo de fabricación donde la huella de carbono es mínima; muchos de ellos se elaboran manualmente en laboratorios, y aquellos que se producen industrialmente generan bajas emisiones de CO2. Este trabajo se centra en el estudio de las cualidades y posibilidades de organismos vivos del reino Fungi para la elaboración de piezas biofabricadas que demuestran propiedades mecánicas, térmicas y estéticas. Se exploran las opciones que ofrece este mundo en sus diversas especies y su interacción con las biomasas vegetales de las que se alimentan para la creación de nuevos materiales. Se brinda una opción material aplicable a la arquitectura con un enfoque sustentable, orientada a la reutilización de residuos en abundancia material, que puedan inscribirse en una economía circular y el concepto de territorio.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2024-1898; Biomaterial; Biofabricación; Biodegradable; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18964